Development of doctoring apparatus capable of measurement and control of doctoring angle and force in printing equipment for printed electronics. (2nd August 2018) - Jeon, Sungwoong; Kim, Cheol; Kim, Chung Hwan
Abstract: The quality of patterns that form printed electronic devices determines their performance and reliability. A doctoring process is necessary in contact printing, and directly affects the quality of the patterns. The doctoring angle and force are controllable parameters among doctoring conditions, in contrast to uncontrollable process-related parameters such as ink properties and printing speed. We developed a doctoring apparatus with a rotational motion-type blading unit that can exert a larger doctoring force to the plate than a linear motion-type blading unit by applying the bending moment to the blade. It can also control and measure the doctoring angle and force, whose values are provided without requiring additional measuring devices such as a camera and load cell. The doctoring angle decreases with increasing doctoring force; therefore, the doctoring angle is defined at the deformed state for more accurate measurement. An estimation method for the doctoring angle using a mathematical model based on the geometric relationships between the design parameters of the blade unit is developed and verified through comparison with direct measurements from photographs. To estimate the doctoring force, the torque feedback signal of the servo motor for the rotational motion of the blade unit is used and calibrated by a direct measurement device equipped with a load cell. The effect of the doctoring angle and force on the quality of the patterns is experimentally examined by assessing the printed patterns obtained in a roll-to-roll gravure printing process. The quality of the patterns is very sensitive to the combination of the doctoring force and angle, and can be enhanced by varying this combination. Therefore, the doctoring angle and force used in the printing process should be measured precisely and controlled appropriately to achieve high-quality printed patterns.